ANALISIS SURVIVAL PENDERITA HIV/AIDS DI RSUD PROF. DR. SOEKANDAR KABUPATEN MOJOKERTO - Nurwidia Arum, Monika Julian; KARTININGRUM, Eka Diah; Fardiansyah, Arief (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
The problem of HIV / AIDS is likened to an iceberg phenomenon that looks just at the top of the mountain. However, this can be seen from the increasing number of HIV / AIDS sufferers who are reported annually. The purpose of this study was to analyze the relationship between the factors that influence the life expectancy of people living with HIV / AIDS in RSUD Prof. Dr. SOEKANDAR, Mojokerto Regency. This study uses the Cohort method with the sampling technique used is total sampling with the object of research amounting to 100 people with HIV / AIDS. Total sampling is the sampling of all members of the population, this is done if the number of members of the population is very limited, so forced to take all members of the population to be representative. Data collection techniques in this study are interviews or interviews, documentation and questionnaires. Data were analyzed by Survival Analysis test using Cox Regression method. The study was conducted in March 2018 until April 2018. The results showed that the most sufferers of HIV / AIDS in RSUD Prof. Dr. SOEKANDAR male sex was 81 people, most patients aged between 25 years to 49 years were 56 people, had opportunistic infections as many as 64 people, 55 people with HIV / AIDS had levels of adherence to antiretroviral drugs more than 95% and risk factors for transmission most of them are heterosexual behavior. Calculation of statistical analysis of Survival Analysis with Cox Regression method found that ARV adherence alone affected the survival of HIV / AIDS sufferers, while age (p value = 0.187), gender (p value = 0.368), incidence of opportunistic infections (p value = 0.669) and Factor for risk of transmission (p value = 0.981) does not affect the survival of HIV / AIDS sufferers. ARV therapy is a therapy that can inhibit the development of the HIV virus in the body. It is expected that people with HIV / AIDS in RSUD Prof. Dr. SOEKANDAR Mojokerto district has adherence to ARV therapy because it can improve survival since being sentenced by the HIV virus.Keywords: Survival, HIV, AIDS